(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper presents a morpho-syntactic approach to inflection as suggested under the new Minimalist Program (Chomsky 1993/1995). The language under consideration is Toposa, an Eastern Nilotic language which is highly inflectional and derivational. It belongs to the Teso-Turkana subgroup of Eastern Nilotic and is spoken in the south-eastern corner of Southern Sudan. Firstly, the paper deals with inflection in a VSO language and suggests that the order of the tense and agreement heads is alternated. The change in the order of heads is morphologically motivated by the tense tonal features of the language. Secondly, it makes a choice between the agreement analysis and the subject incorporation theory, showing that the latter theory reflects more accurately the reality of Toposa data. Thirdly, it considers the role of the overt NP in the subject incorporation theory. It concludes with the claim that the occurrence of personal pronouns carries a [+focus] feature.